Outcomes of ABO-incompatible kidney transplants with very high isoagglutinin titers: a single-center experience and literature review - Naciri Bennani, Hamza; Bobo Barry, Kadiatou Mamadou; Noble, Johan; Malvezzi, Paolo; Jouve, Thomas; Rostaing, Lionel (Frontiers in Immunology, 2024)
BackgroundABO-incompatible kidney transplantation (ABOi-KTx) represents a possible solution to address the shortage of kidney donors. However, these transplants present immunological challenges, particularly when isoagglutinin titers are elevated pretransplant.MethodsSingle-center retrospective study describing clinical and biological outcomes of 8 patients who underwent ABOi-KTx with initial isoagglutinin titers ≥ 1/512. All patients followed a desensitization protocol combining immunosuppression (rituximab, tacrolimus, mycophenolate mofetil, steroids), and specific or semi-specific apheresis sessions. Clinical and biological data were extracted from electronic medical records.ResultsThere were 5 males; median age of 62 years [34-82 years]; all achieved an isoagglutinin titer of ≤1/8 before transplantation after a median of 13 (range: 9-15) apheresis sessions. Three patients (37%) experienced acute humoral rejection, which required additional plasmapheresis sessions. Two patients developed chronic active rejection, successfully treated. On the infectious side, three patients developed BK-virus reactivation. Two patients developed cytomegalovirus viremia, and two others presented with bacterial infections. Surgically, two patients developed a lymphocele, and one had a perirenal hematoma. All patients survived the transplant with stable renal function: mean serum creatinine was 138 ± 15 µmol/L after four years of follow-up.ConclusionABO-incompatible kidney transplantation, even in patients with high isoagglutinin titers, is feasible and can achieve favorable long-term graft and patient survival outcomes. However, these procedures require substantial clinical expertise and close follow-up to monitor and manage the elevated risks of infection and rejection in this population.